Chemosynthetic bacteria found in bivalve species from mud volcanoes of the Gulf of Cadiz - Rodrigues, Clara F.
As in other cold seeps, the dominant bivalves in mud volcanoes (MV) from the Gulf of Cadiz are macrofauna belonging to the families Solemyidae (Acharax sp., Petrasma sp.), Lucinidae (Lucinoma sp.), Thyasiridae (Thyasira vulcolutre) and Mytilidae (Bathymodiolus mauritanicus). The delta 13C values measured in solemyid, lucinid and thyasirid specimens support the hypothesis of thiotrophic nutrition, whereas isotopic signatures of B. mauritanicus suggest methanotrophic nutrition. The indication by stable isotope analysis that chemosynthetic bacteria make a substantial contribution to the nutrition of the bivalves led us to investigate their associated bacteria and their phylogenetic relationships based on comparative 16S rRNA gene sequence analysis. PCR-denaturing gradient gel electrophoresis analysis and cloning of bacterial 16S rRNA-encoding genes confirmed the presence of sulfide-oxidizing symbionts within gill tissues of many of the studied specimens. Phylogenetic analysis of bacterial 16S rRNA gene sequences demonstrated that most bacteria were related to known sulfide-oxidizing endosymbionts found in other deep-sea chemosynthetic environments, with the co-occurrence of methane-oxidizing symbionts in Bathymodiolus specimens. This study confirms the presence of several chemosynthetic bivalves in the Gulf of Cadiz and further highlights the importance of sulfide- and methane-oxidizing symbionts in the trophic ecology of macrobenthic communities in MV.